A Mathematical Model for Classifying the forest Types with Particular Reference to Himachal Pradesh - Suri, S. K. (Indian Forester, 1984)
The classification of the Forest types on the basis of the Floristic composition and the distribution pattern of species, in quantitative term, has great potential. A Mathematical model for such classification has been presented and its advantages have been described in this paper.